2019
DOI: 10.1103/physreve.100.022118
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear fluctuating hydrodynamics with many conserved fields: The case of a three-dimensional anharmonic chain

Abstract: We propose a model for a chain vibrating in 3 dimensions (3D), with first neighbors anharmonic interatomic potential which depends on their distance, and subjected to an external tension.In the framework of the non-linear fluctuating hydrodynamic theory (NLFHT), that was successfully applied to 1D chains, we obtain a heat mode, two longitudinal and four transverse sound modes. We compute their spatio-temporal correlations comparing the theoretical results with molecular dynamics simulations, finding a good agr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Conclusions.-We showed that different atomistic approaches, MD and ALD-BTE, independently provide the evidence that the thermal conductivity of SWCNTs has a finite bulk limit, in contrast with anomalous transport observed in 1D models in 3D space [69]. This result does not conflict with experimental observations of increasing κðLÞ for mm-long nanotubes, as the computed convergence length at RT is beyond 1 mm.…”
mentioning
confidence: 52%
“…Conclusions.-We showed that different atomistic approaches, MD and ALD-BTE, independently provide the evidence that the thermal conductivity of SWCNTs has a finite bulk limit, in contrast with anomalous transport observed in 1D models in 3D space [69]. This result does not conflict with experimental observations of increasing κðLÞ for mm-long nanotubes, as the computed convergence length at RT is beyond 1 mm.…”
mentioning
confidence: 52%
“…Conclusions. We showed that different atomistic approaches, MD and ALD-BTE, independently provide the evidence that the thermal conductivity of SWCNTs has a finite bulk limit, in contrast with anomalous transport observed in 1D models and polymer chains [64,65]. This result does not conflict with experimental observations of increasing κ(L) for mm-long nanotubes, as the computed convergence length at RT is beyond 1 mm.…”
mentioning
confidence: 55%
“…This finding would be ubiquitous in general anharmonic chains with three conserved fields, as studying the widely considered FPUT systems with vanishing and nonvanishing pressure leads to similar observations. Viewing all of these findings, it would be of interest to extend the present scheme to study other systems like the one having more degrees of freedom [30], or the system with a strong external pressure [13]. In the latter system it was argued that the pressure fluctuations can cause the recovery of the Fourier law due to the crossover between two fixed points in FHD.…”
Section: Conclusion and Discussionmentioning
confidence: 91%